Carry on [compact disc, unabridged] : the rise and fall of Simon Snow - Rowell, Rainbow (Macmillan Audio, 2015)
During his last year at Watford School of Magicks, Simon Snow, the Chosen One, faces a magic-eating monster wearing his face, a break-up, and a missing nemesis.